1997
DOI: 10.2307/3433304
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphisms of H-ras-1 and p53 in Breast Cancer and Lung Cancer: A Meta-Analysis

Abstract: 919-926 (1997)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
25
0
1

Year Published

2000
2000
2009
2009

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 49 publications
4
25
0
1
Order By: Relevance
“…These changes in conjunction with certain environmental exposures (e.g., smoking, lung cancer) may increase the risk for cancer development in people with susceptible genotypes. However, these studies have been inconsistent, most likely because of a number of factors, including racial frequency differences between cases and controls, varied population bases, and lack of Hardy-Weinberg equilibrium in some examined cases (15)(16)(17)(18)(19)(20). In our opinion, these variables and others account for the discrepant results between independent studies examining the polymorphism of p53 at codon 72 and carcinogenesis.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…These changes in conjunction with certain environmental exposures (e.g., smoking, lung cancer) may increase the risk for cancer development in people with susceptible genotypes. However, these studies have been inconsistent, most likely because of a number of factors, including racial frequency differences between cases and controls, varied population bases, and lack of Hardy-Weinberg equilibrium in some examined cases (15)(16)(17)(18)(19)(20). In our opinion, these variables and others account for the discrepant results between independent studies examining the polymorphism of p53 at codon 72 and carcinogenesis.…”
Section: Discussionmentioning
confidence: 84%
“…Ethnic differences in these allelic frequencies exist as well (14). In the U.S. population, the proline allele is identified more commonly in African Americans (61%) than in Caucasians (34%) (13)(14)(15).…”
mentioning
confidence: 99%
“…Although biochemically different, the significance of the p53 codon 72 polymorphism remains controversial in terms of cancer epidemiology. Significant association between the codon 72 polymorphism and risk of cancer had been reported, although the results with regard to most cancer diseases, including breast cancer, remain inconclusive (7)(8)(9). Nonetheless, it is possible that the differences between various reports can reflect the populations that were analyzed, as there are inherent differences in the relative prevalence of the polymorphic alleles in various populations (10).…”
Section: Introductionmentioning
confidence: 82%
“…By contrast, the Trp53 72R allele was preferentially expressed in most heterozygote breast cancer patients . These data, together with the many reports indicating that the Trp53 72R was associated with cancer predisposition (Sja¨lander et al, 1996;Weston and Godbold, 1997;Papadakis et al, 2000;Bergamaschi et al, 2003), suggested to us that although the Trp53 72R form might be capable of inducing apoptosis better, it might not be efficient in preventing cancer formation. We have therefore investigated if the two different Trp53 variants would have differential ability to regulate DNA-repair, a process that is regulated by Trp53 and that is essential for the prevention of accumulation of genomic instability and hence, cancer formation (Risinger and Groden, 2004;Sengupta and Harris, 2005 (Figure 1a), excluding the possibility that differential expression may account for the observed transactivation differences.…”
Section: P -Expressing Cells Exhibit Reduced Micronuclei Formation mentioning
confidence: 88%